TRGET: geração de traces para simulação de VANETs por meio de redes de Petri coloridas - Vasconcelos, Luís César Marques de (2018)
Vehicular ad hoc networks (VANET) have the potential to increase road safety and pro- vide network services for passengers. VANETs enable the creation of applications such as: congestion detection, detection of road conditions, accident detection, monitoring and automatic fines collection, assistance and entertainment. Performing tests in real sce- narios is an arduous task due to issues such as high economic cost, making simulation the best way to perform performance analysis. In this work, we introduce the TrGeT model developed in timed hierarchical coloured Petri nets that generates mobility traces to simulate VANETs in network simulators. The scenarios configuration for generation of traces is carried out in a simplified way and without the need of knowledge of traffic and urban mobility simulators. The performance evaluation of the tool shows the effectiveness of the generated mobility traces.